Peha-haft bandage as a new dressing for pediatric hypospadias repair - Gangopadhyay A; Sharma S (Indian Journal of Plastic Surgery)
Hypospadias Repair has varied alternatives in every step including dressing. Objective: To compare Peha-Haft cohesive dressing with compressed gauze penile wrap dressing in hypospadias repair. Patients and methods: Peha-Haft cohesive dressing was prospectively used in 60 subjects (Group A) over a period of three and a half years from Jan.2001 to July 2004 and compared with 60 subjects of compressed gauze dressing with micropore adhesive (Group B). Primary outcome measures were ease of application, cost, comfort with dressing, dressing related early complications, pain during dressing removal assessed by FLACC score and time taken during removal. Results: Time taken during dressing removal was 30 + 11 seconds in Group A and 180 + 26 seconds in Group B. FLACC score was 3 + 2 in Group A and 7 + 3 in Group B. No sedation was required in the Group A while it was required in 26 cases in Group B Conclusion: Peha-Haft dressing was superior in terms of the ease of application, cost, comfort with dressing, dressing related early complications, time consumed and pain during dressing removal.